THE EFFECT OF (Morinda citrifolia L.) MEAL IN DIET ON PERFORMANCE OF BROILER - Yosi Fenita (BPFP Faperta UNIB, 2012)
The objective of the research was to evaluate to effect of feeding mengkudu on performances of broilers. The research design used was completely randomized design. One hundred broilers were distributed into five treatments. The treatments were different levels of mengkudu meal (0, 0.75%, 1.5%, 2.25 % and 3%). The observed measured were feed consumption, average body weight (gain) and feed conversion. Results showed that feeding mengkudu (Morinda Citrifolia L.) no effect significant (P>0.05) on feed consumption, average body weight and feed conversion. In conclusion, feeding mengkudu meal up to 3% (in diet) does not negatively affect feed consumption, average body weight, and feed conversion.